DIAGNOSTIC MARKERS AND CYTOKINE PROFILE IN PATIENTS WITH RHEUMATOID ARTHRITIS RECEIVING DMARDS - Maria Sergeevna Voronina; A A Vinogradov; N P Shilkina (Научно-практическая ревматология)
Objective — to evaluate the relationship between antibody titers against modified citrullinated vimentin (AMCV), IgM rheumatoid factor (RF), interleukin (IL) 4, IL6 and IL8, and their correlation with rheumatoid arthritis (RA) activity indicators, systemic manifestations, evolution of disease activity and functional status in patients treated with methotrexate (MT). Material and methods. 76 RA patients were evaluated: 44 — were on MT, 32 — were not receiving DMARDs for <3 months. Serum IgM RF and C-reactive protein (CRP) levels were measured by immunonephelometry, AMCV, IL6, IL8 (ng/Ml) — by solid-phase immunoenzyme analysis. Results. There was no correlation between AMCV levels and RA activity measures (p>0,05). Higher AMCV titers were detected in patients with systemic manifestations vs patients without such symptoms (p=0,002). In subgroup of patients with baseline AMCV >500 U/Ml a significantly lower level of IL6 was observed (p=0,03) with a tendency for AMCV level reduction (p=0,06) and an increase in DAS28 scores after 12 mo of MT therapy (p>0,05). IgM RF titers were significantly higher in patients with high disease activity (p=0,0006) and in patients with systemic manifestations (p=0,04). Significantly higher IL6 levels (p=0,01) and a tendency to DAS28 measures reduction after 12 mo of MT therapy was observed in patients with baseline IgM RF >100 IU/Ml (p>0,05).